Meningkatkan Pemahaman Agama Masyarakat Desa Melalui Majelis Taklim - Galang Prasetyo; Solfema Solfema; Lili Dasa Putri (Lembaga Pengembangan Kinerja Dosen, 2025)
This article discusses how the Majelis Taklim can help rural communities better understand religion. Majelis Taklim plays an important role in realizing the religious knowledge of rural communities. Majelis Taklim has many forms and ways to be implemented. These Majelis Taklim can empower rural communities by spreading sustainable Islamic knowledge. They increase people's understanding of Islamic teachings and improve the quality of their worship. These Majelis Taklim instill moral and ethical principles that can be applied in daily activities. through continuous coaching.